COMPREHENSIVE APPROACH TO TREATMENT OF EXOGENOUS- CONSTITUTIONAL OBESITY IN CHILDREN - Yu.V. , Vladimirova; V.A, Zhirnov; O.V., Sazonova; M.Yu., Gavryushin; D.O., Gorbachyov (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we presented a new tactic for managing children with exogenous-constitutional obesity against the background of leptin resistance. Body weight in children with and without leptin resistance did not differ statistically, but the degree of reduction in the 1 to 3 course of therapy was more expressed in children in the comparison group, without leptin resistance. So in the comparison group after the 1st course, the weight decreased by 2.27±0.78 kg, and in the main group - by 1.63±0.56 kg (p